The effect of hypermobility on the incidence of injury in professional football: A multi-site cohort study. (September 2016) - Konopinski, Matt; Graham, Ian; Johnson, Mark I.; Jones, Gareth
Abstract: Background: A recent study demonstrated joint hypermobility increased the incidence of injury in an elite football team utilising a univariate statistical model. Objectives: To compare injury incidence between hypermobile and non-hypermobile elite football players incorporating a multi-site design and multivariate inferential statistics. Methods: 80 players comprising 3 English Championship football teams were followed prospectively during the 2012–2013 season. Joint hypermobility was assessed according to the 9-point Beighton Criteria at the start of the study period. A cut-off score of ≥4 categorised a participant as hypermobile. Player exposure and time-loss injuries were recorded throughout. Results: Mean ± standard deviation incidence of injuries was 9.2 ± 10.8 injuries/1000 h. The prevalence of hypermobility was 8.8%. Hypermobiles had a tendency for higher injury incidence (mean [95% confidence interval] difference, 5.2 [0.9–2.7] injuries/1000 h; p = 0.06). Cox regression analyses found training exposure to be highly significant in terms of injury risk ( p < 0.001) for all participants. Non-hypermobiles had a lower injury risk ( p = 0.11), according to the Cox model, which is suggestive but not conclusive that hypermobility predisposes injury risk. Conclusions: Hypermobility showed a trend towards increased risk of injury. Training exposure is a significant injury risk factor in elite football. Highlights: Results suggest that hypermobility increases injury risk in elite footballers. Medical staff should consider routine screening of footballers for hypermobility. Training exposure is a significant injury risk factor for elite football players.